Flow and hardening behavior in the heat-affected zone of welded ultra-high strength steels - Afkhami, Shahriar (Springer Nature, 2025)
The applications of thermomechanically processed ultra-high strength steels (UHSS) are rapidly increasing, and welding these UHSSs seems inevitable in steel structures. However, welding heat causes unwanted microstructural transformations in the heat-affected zone (HAZ). Due to the localized nature of these changes throughout the HAZ, evaluating the true stress-strain values of these localized HAZ subzones is essential to improve the accuracy of analytical or numerical models. Hence, this study utilized experimental thermal simulations to replicate HAZ subzones of two types of UHSSs, i.e., direct-quenched S960 and quenched-and-tempered S1100, and employed tensile test in conjunction with digital image correlation to plot the true stress-strain and hardening curves of the subzones. Both UHSSs manifested similar trends but with various fluctuations in their hardening capacities throughout their HAZ subzones. Next, hardening parameters from Hollomon, Voce, and Kocks-Mecking approaches were extracted by fitting the experimental results with the semi-empirical equations. For both UHSS types, the Voce approach, on average, was more accurate in modeling the plastic deformation. Also, hardening parameters achieved via the Voce approach's fittings agreed with the parameters from Kocks-Mecking plots; this consistency pointed to the predictability of the plastic flow and hardening behavior of both UHSS types. According to the microstructural investigations, the hardening behavior of the investigated HAZ subzones depended on two types of microstructure constituents: ferritic and lath-like features. Ferritic features dominantly governed the plastic flow and hardening near the fusion line, while by getting distant from the fusion line, the lath-like features became more dominant.